From Traditional Employment to Gig Work: Analyzing Labor Dynamics in Nepal’s Emerging Gig Economy - Sagar B.K.; Niranjan Devkota; Smeeth Bista (Journal of Development and Administrative Studies, 2024)
This study explores the sustainability of labor participation in Nepal’s gig economy, focusing on the Kathmandu Valley, with an emphasis on identifying factors influencing gig participation across ride-sharing, online tutoring, e-commerce delivery, food delivery, and freelancing platforms. A binary logit regression model was employed to analyze survey data from 386 gig workers. Statistical robustness was ensured through normality tests, correlation matrices, multicollinearity, heteroskedasticity checks, and sensitivity analyses. The results reveal that employment status significantly enhances the likelihood of gig economy participation, with a log-odds ratio of 5.469 (p < 0.01), indicating that employed individuals are over five times more likely to engage in gig work. Work satisfaction is positively correlated with participation (odds ratio = 3.147, p < 0.01), suggesting that satisfied workers are approximately three times more likely to take on gig roles. Employment and work satisfaction increase participation likelihood by 20.5% and 13.8%, respectively. Conversely, participation in e-commerce delivery and ride-sharing platforms is negatively correlated. Monthly income generally reduces participation, except in food delivery platform. Policy implications emphasize the need for enhanced legal protections, income stability, and platform transparency. Regulations ensuring job security, flexible scheduling, and supportive measures like tax incentives are vital to creating a sustainable and inclusive gig economy in Nepal.